Implementing and Monitoring Water Consumption Using IoT-Based Smart Dispensers - Dasmen, Rahmat Novrianda; Yahya, M. (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2024)
Conventional dispensers have limitations in providing drinking water tailored to user preferences and do not focus on efficient resource use. This research aims to address these issues by designing and implementing a smart, efficient automatic dispenser. An experimental method was used to develop an Arduino-based prototype consisting of several components: flow sensor, color sensor, fingerprint sensor, proximity sensor, DC pump, motor driver, NodeMCU, and LCD. The flow sensor measures water volume, the color sensor detects glass color, the fingerprint sensor identifies the user, and the proximity sensor detects the presence of the glass. The DC pump flows water from the tank to the glass, relays and solenoids control the water flow, NodeMCU processes sensor data and connects to IoT, and the LCD displays the required information. A battery backup ensures functionality during power outages. The research results show that the automatic dispenser performs well and meets the research objectives. It provides drinking water according to user preferences: warm water for red glasses, cold water for blue glasses, and room temperature water for green glasses. Additionally, it identifies users through fingerprints and sends notifications via Telegram chatbots. This smart dispenser offers a more efficient and user-friendly solution compared to conventional dispensers.